Comparison between Neurocysticercosis (NCC) and Central Nervous System (CNS) Tuberculoma in Children: Dilemma over Clinico-Radiological Diagnosis? - Bharat Bhushan Sharma; Shashi Sharma; Natasha Nargotra; Nalin Chugh; Ritu Dhaka (Highlights on Medicine and Medical Science Vol. 7, 2021)
Background: Neurocysticercosis (NCC) and central nervous system (CNS) tuberculomas often overlap in clinical presentation and imaging. Though the aetio-pathology entirely differs in both the scenarios but there is great confusion in their clinico-radiological evaluation as the findings and appearances are similar in many ways. The stress should be laid out over the salient features of each entity in the back- ground of their presentation. The study was conducted to highlight the differentiation of the clinico-radiological findings in both the entities. Materials and Methods: Ten patients between 5 - 15 years (mean age 10.4 years) with complaints of headache and with or without seizures had undergone MRI alone or with CT examinations. Basic sequences of T1W, T2W, T2W FLAIR and T1W contrast studies were carried out in all the cases. CT was carried out in only three cases and contrast was given in two cases. Results: Eight patients were having ring enhancing lesions in post contrast studies in MRI and two had only cystic lesions ranging from 1 - 3 cm in diameter. Conclusion: Seven cases having tuberculomas were confirmed by both the modalities with one case inconclusive. Two cases were diagnosed as neurocysticercosis as per the results. The reasonable achievable target was the goal to differentiate between NCC and tuberculomas in the brain and it was achieved. Contrast MRI and spectroscopy brought out many findings for the distinct features in many cases. MR spectroscopy findings show lipid peak in the former and amino acid peak in the later.